2018
DOI: 10.5009/gnl18220
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Nab-Paclitaxel Plus Gemcitabine and Prognostic Value of Peripheral Neuropathy in Patients with Metastatic Pancreatic Cancer

Abstract: Background/AimsThe combination of nab-paclitaxel and gemcitabine (nab-P/Gem) is widely used for treating meta-static pancreatic cancer (MPC). We aimed to evaluate the therapeutic outcomes and prognostic role of treatment-related peripheral neuropathy in patients with MPC treated with nab-P/Gem in clinical practice.MethodsMPC patients treated with nab-P/Gem as the first-line chemotherapy were included. All 88 Korean patients underwent at least two cycles of nab-P/Gem combination chemotherapy (125 and 1,000 mg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Also considering the higher ORR and survival in our study, there may be room for modification in the chemotherapy regimen with further optimized and well-balanced oncologic benefits and adverse events. The prognostic role of treatment-related peripheral neuropathy was limited during nab-paclitaxel plus gemcitabine treatment for patients with metastatic pancreatic cancer (30), and the replace of gemcitabine with S-1 is expected to be associated with safer profiles. While generally manageable, various adverse events during treatment call for meticulous and specific monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…Also considering the higher ORR and survival in our study, there may be room for modification in the chemotherapy regimen with further optimized and well-balanced oncologic benefits and adverse events. The prognostic role of treatment-related peripheral neuropathy was limited during nab-paclitaxel plus gemcitabine treatment for patients with metastatic pancreatic cancer (30), and the replace of gemcitabine with S-1 is expected to be associated with safer profiles. While generally manageable, various adverse events during treatment call for meticulous and specific monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…In a Korean cohort study, Cho et al reported CIPN in more than 50% of patients, and 15 (18.5%) of these patients experienced severe grades of toxicity [ 8 ]. In the study by You et al, 13 (14.8%) patients developed grade 2 PN, while 16 (18.2%) developed grade 3 PN; 19.3% and 18.2% of all patients needed dose reduction and discontinuation of treatment due to PN, respectively [ 37 ]. In our study, 47 patients (30.7%) experienced grade 1–2 CIPN, and of these, 38 (80.8%) required dose reduction, and 30 (44.7%) discontinued treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al highlighted the presence of neurologic adverse events as independent survival prognostic factors (HR 0.302; 95% CI 0.130–0.702, p = 0.005) [ 8 ]. You et al reported a significantly longer survival rate in patients with CIPN compared to those without neuropathy in the naive model (10.13 vs. 15.53 months, p = 0.007), although this correlation was not confirmed in the landmark model at 6 months, used to reduce lead time bias (11.4 vs. 15.3 months) ( p = 0.089) [ 8 , 23 , 37 ]. Various studies of breast cancer have been conducted to identify clinical or molecular risk factors for the development of chemotherapy-induced neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Overall survival was longer in patients with CIPN than in patients without CIPN. In 2018, You et al 58) reported that OS was longer in metastatic PC patients with neuropathy ( n = 52, 15.53 months) than in metastatic PC patients without neuropathy ( n = 36, 10.13 months, p value = 0.007). In 2021, Catalano et al 59) reported that the median OS was 13 months and 10 months in metastatic PC patients with ( n = 47) and without grade 1-2 CIPN ( n = 106) ( p value = 0.04).…”
Section: Drug Treatmentmentioning
confidence: 99%
“…Patients with longer OS are administered more anticancer drugs; therefore, the OS of PC patients with CIPN might be longer than the OS of PC patients without CIPN. However, some PC patients with CIPN discontinued chemotherapy 58 , 60) . Therefore, CIPN should be treated by the treatment described above.…”
Section: Drug Treatmentmentioning
confidence: 99%